Rifaximin for Pertuzumab-Related GI Toxicities - Soyano, Aixa E.; Reynolds, Gina; Moreno-Aspitia, Alvaro; Chumsri, Saranya (Frontiers in Oncology, 2017)
Pertuzumab is a monoclonal antibody against HER-2. Diarrhea and abdominal pain are common adverse events of pertuzumab-based therapy, occurring in almost 70% of patients. The incidence of gastrointestinal toxicities intensifies when pertuzumab is given in combination with chemotherapy. Rifaximin, a non-absorbable oral antibiotic, may provide symptomatic relief in patients with refractory gastrointestinal toxicities from pertuzumab-based therapy beyond standard routine antidiarrheal medications. We present a case of HER-2 related therapy induced diarrhea and abdominal pain managed successfully with Rifaximin.